Co-infection of the respiratory epithelium, scene of complex functional interactions between viral, bacterial, and human neuraminidases - Escuret, Vanessa; Terrier, Olivier (Frontiers in Microbiology, 2023)
The activity of sialic acids, known to play critical roles in biology and many pathological processes, is finely regulated by a class of enzymes called sialidases, also known as neuraminidases. These are present in mammals and many other biological systems, such as viruses and bacteria. This review focuses on the very particular situation of co-infections of the respiratory epithelium, the scene of complex functional interactions between viral, bacterial, and human neuraminidases. This intrinsically multidisciplinary topic combining structural biology, biochemistry, physiology, and the study of host-pathogen interactions, opens up exciting research perspectives that could lead to a better understanding of the mechanisms underlying virus-bacteria co-infections and their contribution to the aggravation of respiratory pathology, notably in the context of pre-existing pathological contexts. Strategies that mimic or inhibit the activity of the neuraminidases could constitute interesting treatment options for viral and bacterial infections.